A new species of Cicadatra Kolenati, 1857 from China, with primary phylogenetic analyses of the tribe Cicadatrini (Hemiptera: Cicadidae) - Wang, Xu; He, Zhiqiang; Wei, Cong (Zootaxa, 2017)
A new species of the genus Cicadatra Kolenati, 1857, C. hei sp. nov., from Sichuan Province, China is described. A key to the species of Cicadatra from China is provided. Morphological characters for 9 taxa of the tribe Cicadatrini and for 3 outgroup taxa are examined to present the first phylogenetic reconstruction within the Cicadatrini. The monophyly of Cicadatrini is supported, and Cicadatrini is more allied to the outgroup Cicadetta of the subfamily Cicadettinae (= Tibicininae auct.) from TNT and WinClada analyses. The systematic status of the tribe Cicadatrini is discussed. The genus Cicadalna Boulard, 2006 is recognized to be a junior synonym of Emathia Stål, 1866, and Cicadalna takensis Boulard, 2006 is transferred from Cicadalna to Emathia to become Emathia takensis (Boulard, 2006) comb. nov.